A catheterizable serous-lined urinary outlet associated with the ileal bladder augmentation Abol-Enein and Ghoneim procedure: a safe and reliable procedure in children - Alliot, Hortense; Tapsoba, Toussaint; Paye-Jaouen, Annabel; Ashkanani, Yaqoub; Josset-Raffet, Eliane; Natio, Lise; Peycelon, Matthieu; El-Ghoneimi, Alaa (Frontiers in Pediatrics, 2024)
Purpose: To evaluate the long-term outcome of the serous lined extramural continent catheterizable outlet procedure (SLECCOP) associated with ileal bladder augmentation in children. Methods: Monocentric and retrospective study (2002-2021), including children (<18 years) undergoing SLECCOP associated with W-shaped ileocystoplasty with catheterizable channel (Abol-Enein & Ghoneim procedure). Exclusion: other type of bladder augmentation or W- shaped ileocystoplasty without catheterizable channel. Patient records were reviewed for demographics, surgical data, long-term outcomes. Results: Fifty-two children (33 boys, median age: 8.5 [0.8-18] yr). Pathology included 28 BEEC, 11 neurogenic bladders, 12 others. Two patients had total bladder substitution. Thirty- four (65%) patients had BNR including 23 associated with SLECCOP and ileocystoplasty and 11 prior BNR. All stomas but two were umbilical, associated with omphaloplasty in 28 BEEC. Forty were appendix (77%), 12 Monti tube (23%). Stoma complications were cutaneous strictures (n=2, 4%) and leaks (n=10, 19%), all treated by Dx/HA injection (n=10). Redo surgery was required in 3 patients: extraserosal wrapping for persistent leak (n=2, 4%), surgical revision of Monti (n=1, 2%). Three patients (6%) had dilatation for transient stoma stenosis. Leaks occurred in 20% of appendix channels (n=8/40) and 17% of Monti tubes (n=2/12). Strictures occurred in 3% of appendix channels (n=1/40) and 8% of Monti tubes (n=1/12). Bladder stones occurred in 4 patients (8%). Channels leaks remained in 1 patient (2%) at median follow-up of 4.4 years [IQR 1.4-9.7]. Conclusion: W-Ileal bladder augmentation with SLECCOP is an efficient technique for treating children with incontinence of different etiologies. Channel complication rate is very low, specifically for stricture, in this complex group of patients.